Nation, nationality, nationalism:: the current confusion in Colombian music. (The Voz a Vos Bulletin, 2023)
Reflection on how the evolution of our identity as a nation influences the way of thinking about traditional music, from the national policies that arise from our cultural processes, our ideas of nation and nationality.